Pulmonary adenocarcinoma in cattle - Diogo Sousa, Z. [UNESP]; Luis Rivera, C. [UNESP]; Didier Quevedo, C. [UNESP]; Gorino, Ana Claudia [UNESP]; Simone Biagio, C. [UNESP]; Renée Laufer, A. [UNESP] (My University, 2014)
The Macroscopic, histological and immunohistochemical aspects of lung acinar adenocarcinoma and the presence of nodules in the abdominal cavity of an adult female bovine are reported. In the necropsy analysis samples were collected from the: lung, heart, spleen, liver, pancreas, kidney, uterus, intestine, brain, and from nodules found in the lung and abdominal cavity, which were routinely processed to be stained by hematoxylin-eosin and for an immunohistochemistry exam with the antibodies: cytokeratin (dilution 1:200 μL) and vimentin (dilution 1:1000 μL). The histopathological examination revealed neoplastic epithelial cells with acini formation. The immunohistochemical examination of the tumor cells showed positive marking for cytokeratin and the absence of marking for vimentin. According to anatomical, morphological, and histopathological findings, as well as the result of the immunohistochemical examination, the tumor was characterized as lung acinar adenocarcinoma.
Adenocarcinoma pulmonar en bovinos
Keywords: Histopathology; Immunochemistry; Lung; Metastasis; Neoplasia (source: cab)